2018
DOI: 10.1177/1049732318803590
|View full text |Cite|
|
Sign up to set email alerts
|

Individuals With the Rare Disease Pemphigus: A Quest for Diagnostic

Abstract: This qualitative study conducted in France of “individuals living with a pemphigus” (ILPs; N = 54) highlights the taxing diagnostic trajectory of those suffering from these rare autoimmune diseases. Beyond enduring a diagnostic period that may prove long, during their numerous medical appointments, these individuals internalize the expectations of the medical professionals who are treating them. In some cases, numerous inconclusive medical tests and, at times, a doctor’s condescension may push the patient towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…A significant number of the most socially privileged participants in our study favour psycho‐corporeal practices that are done alone and are understood as time for oneself. The rarity of their little‐known illness may explain this withdrawal: it is difficult to speak openly of it without running the risk of being misunderstood (Le Hénaff and Héas ), which explains why they would want to avoid social spaces where it is more difficult to manage information. This interest is furthermore consistent with the exponential development of this kind of activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant number of the most socially privileged participants in our study favour psycho‐corporeal practices that are done alone and are understood as time for oneself. The rarity of their little‐known illness may explain this withdrawal: it is difficult to speak openly of it without running the risk of being misunderstood (Le Hénaff and Héas ), which explains why they would want to avoid social spaces where it is more difficult to manage information. This interest is furthermore consistent with the exponential development of this kind of activity.…”
Section: Discussionmentioning
confidence: 99%
“…One or two cases per million of pemphigus vulgaris, the most common form, are diagnosed each year in France (Joly and Sin ). This rarity implies a range of challenges, including a dearth of experts and treatments, difficulties getting diagnosis and information, and isolation (Le Hénaff and Héas ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, some of them may decide to change their doctors, which means starting this inconvenient process all over again. 88 This delay in diagnosis is more or less constant among different reports; accordingly, there is an average 6 months lag from the first presentation to definite diagnosis. [89][90][91][92] It is shown that pemphigus in the oral cavity is diagnosed later than on the skin due to more non-specific features of mucosal involvement.…”
Section: Delay In Diagnosismentioning
confidence: 99%
“…Consequently, some of them may decide to change their doctors, which means starting this inconvenient process all over again. 88 …”
Section: Delay In Diagnosismentioning
confidence: 99%
See 1 more Smart Citation